Синтез и свойства крупнозернистого кубического нитрида бора, полученного с использованием дополнительных центров кристаллизации - Боримский, И.А.; Белявина, Н.Н.; Маркив, В.Я. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
High pressure–high temperature synthesis of cBN by various methods has been analyzed.
The possibility is shown to essentially increase the concentration of coarse grains in the synthesis
product if additional crystallization centers are inserted into the growth medium. The morphology
and physico-mechanical properties of coarse-grained cBN powders (of size up to 500 μm) both at
room temperature and on heating at 1000 ⁰C are discussed